PENGARUH RASIO NA₂SIO₃ : NAOH TERHADAP KUAT TEKAN MORTAR GEOPOLIMER ABU SEKAM PADI - abdi nasrullah; Agil (Jurnal Ilmiah BERING, 2022)
This research was conducted to study the influence of rice husk ash and variations in the ratio of alkali activator solution on the compressive strength of geopolymer mortar. Additionally, this study aimed to determine the optimal proportion of rice husk ash and alkali activator ratio for geopolymer mortar, as well as to evaluate the potential of rice husk ash and alkali activator as alternative raw materials for geopolymer mortar production. In the experimental method, the mortar mixture used consisted of rice husk ash that had been filtered using a No.200 sieve, and NaOH:Na₂SiO₃ alkali activator solution with a concentration of 16 M, and weight ratios of NaOH to Na₂SiO₃ of 2, 2.25, and 2.5. The ratio of alkali activator to precursor used was 1:2, and testing was conducted at ages of 3, 7, 14, 21, and 28 days in the Laboratory of the Pagar Alam Higher School of Technology. Based on the research results, it was found that the mixture with a 1:2 ratio had the highest compressive strength in geopolymer mortar, with a value of up to 13.06 MPa at 28 days of age. This indicates that rice husk ash and alkali activator solution can be used as alternative raw materials for geopolymer mortar production, which has a sufficiently high compressive strength. This study provides valuable information for the construction industry in selecting environmentally friendly and sustainable raw materials.